Evaluation of pitch estimation in clean and noisy speech - Satyanarayana Murthy, A; Sairam, P; Sai Kumar, B (International Journal of Engineering and Technology, 2018)
Every human being has a distinct voice due to pitch association and it is almost like a finger print. Pitch is one of the important parameter which is used in many speech processing applications. In reality speech is a complex combination of both voiced and unvoiced sounds and cannot be separated subjectively. For the voiced speech, pitch is defined as the rate of change of vocal folds vibrations. In practice, pitch is a subjective quantity and cannot be measured directly from the voice. It is a non-linear quantity, depends upon the spectral and temporal content of the signal. Many pitch estimation methods have been developed but none can work efficiently in the presence of additive noise. It is very essential to understand the effect of noise on the pitch estimation in dealing effectively with many speech processing applications. Speech processing systems should be robust enough to counter the presence of noise to produce good quality sounds. In non-intrusive speech quality measurement algorithms, pitch is one of the quality parameter for speech assessment. The accuracy of this feature in noisy speech is correlated with the subjective quality of speech. In this paper we have been evaluated the performance of auto-correlation and cepstrum algorithms for pitch estimation and tracking.Â Â